ANALISIS PELAKSANAAN DAN KOMPETENSI PENYULUH PERTANIAN DI KECAMATAN LANGGAM KABUPATEN PELALAWAN - Indra T A Rambe; Rosnita Rosnita; Eri Sayamar (DINAMIKA PERTANIAN, 2015)
This research aims to study the implementation of agricultural extension in Langgam District and to analyse the competence of agricultural extension in Langgam District. This research used survey method. The respondents were the agricultural staff in Langgam District, they were selected by sensus. Data analysis used qualitative analysis and Likert's Summated Rating (LSR). The result showed that the agricultural extension’s implementation in Langgam District were: the number of agricultural extension in Langgam District are 5 people with palm farmers as target ; the method used Training and Visiting ; the media used properties and tools ; the material given of extension suitable with farmer’s need; and the time of extension suitable with agreement. The competence level of agricultural extension in Langgam District was categoried as “very competent” in total of 4.21 score. It is supported by competence of administration, planning of program, implementation of program, teaching and evaluation in “very competent” category. The competence of communication in “competent enough” category with 2.90 score.